Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/asj.12261
|View full text |Cite
|
Sign up to set email alerts
|

Influence of corpus luteum and ovarian volume on the number and quality of bovine oocytes

Abstract: In order to evaluate whether ovarian volume, presence and diameter of the corpus luteum (CL) have effects on the number and quality of bovine recovered oocytes, 110 ovaries were obtained from the slaughterhouse. Cumulus oocytes complex were aspirated and evaluated under stereomicroscope. Oocytes were counted and classified according to their quality (Grades I, II, III and IV). Ovarian volume was weakly correlated to the number of good quality oocytes (P < 0.05). Ovaries with CL showed greater numbers of good q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
1
8
1
2
Order By: Relevance
“…Furthermore, the ovarian follicular reserve can also be evaluated through ovarian volume (OV) (Kwee et al, 2007), which varies in accordance with the reproductive stage, the oestrous phase and the gestation period, and can be used as a parameter in the clinical and functional evaluation of the organ (Chacur et al, 2006). Ovarian volume can be used as a reproductive parameter because it has a direct relationship with hormone production during the oestrous cycle (Penitente-Filho et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ovarian follicular reserve can also be evaluated through ovarian volume (OV) (Kwee et al, 2007), which varies in accordance with the reproductive stage, the oestrous phase and the gestation period, and can be used as a parameter in the clinical and functional evaluation of the organ (Chacur et al, 2006). Ovarian volume can be used as a reproductive parameter because it has a direct relationship with hormone production during the oestrous cycle (Penitente-Filho et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this notion, Pirestani et al [19] reported that oocytes derived from ovaries containing a large follicle (~20 mm) were less competent compared to embryos derived from ovaries that containing a CL. Similarly, Penitente-Filho et al [20] classified cumulus-oocyte complexes (COCs) under the stereomicroscope and indicated that ovaries with CL yielded a greater number of good quality oocytes than ovaries without CL. However, the oocytes used in the latter study were not subjected to IVP to confirm their developmental competence.…”
Section: Ovarian Morphologymentioning
confidence: 99%
“…Hambatan sekresi estrogen dan inhibin oleh progesteron akan menekan pengaruh negatif folikel dominan terhadap pertumbuhan dan perkembangan folikel subordinat lainnya (Parera dan Lenda, 2019). Selain itu hormon progesteron memungkinkan folikel terekspos untuk periode yang lebih lama sebagai akibat dari rendahnya level LH dan hal ini memungkinkan untuk memperoleh oosit yang berkualitas baik (Penitente-Filho et al, 2015). Sebaliknya pada ovarium tanpa CL, tidak adanya kehadiran CL tidak menyebabkan efek negatif progesteron pada hipofisis anterior sehingga kadar estrogen dan progesteron tetap seimbang yang memungkinkan pertumbuhan folikel (Khandoker et al, 2016).…”
Section: Hasil Dan Pembahasan Pengaruh Status Reproduksi Terhadap Kuaunclassified